2007
DOI: 10.1016/j.bbamcr.2007.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of the NADPH oxidase NOX4 is a hallmark of adipocyte differentiation

Abstract: Adipocyte differentiation is a complex process regulated among other factors by insulin and the production of reactive oxygen species (ROS). NOX4 is a ROS generating NADPH oxidase enzyme mediating insulin's action in 3T3L1 adipocytes. In the present paper we show that NOX4 is expressed at high levels both in white and brown preadipocytes and that differentiation into adipocytes results in a decrease in their NOX4 mRNA content. These in vitro results were confirmed in vivo by demonstrating that in intact adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 51 publications
3
60
1
Order By: Relevance
“…It was recently shown that Nox2 and Nox4 each compensate for the deficiency of the other in lung endothelial cells (37). Down-regulation of Nox4 expression is associated with adipocyte differentiation (38), and Nox4 has been proposed to act as a switch that controls the transition between proliferation and differentiation of preadipocytes (39). Our results now suggest that increasing the expression of Nox1 and Nox2 and decreasing the expression of Nox4 are characteristics of chondrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that Nox2 and Nox4 each compensate for the deficiency of the other in lung endothelial cells (37). Down-regulation of Nox4 expression is associated with adipocyte differentiation (38), and Nox4 has been proposed to act as a switch that controls the transition between proliferation and differentiation of preadipocytes (39). Our results now suggest that increasing the expression of Nox1 and Nox2 and decreasing the expression of Nox4 are characteristics of chondrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…NADPH oxidase acts as the source of ROS in MSCs, as evidenced by the observation that Nox4 was downregulated after the induction of differentiation. Also, Nox4 is downregulated in mature adipocytes (57,75). Nox4 thus plays a vital role in adipogenesis from MSCs.…”
Section: Role Of Ros In Multipotent Ascsmentioning
confidence: 99%
“…3B). Because expression of Nox family can be regulated by external stimuli such as hypoxia and insulin treatment [35][36][37], we investigated whether hypoxia modulates mRNA expression of Nox family. However, hypoxia (2% O 2 for 4 and 24 h) did not change the mRNA expression of Nox4, Nox5, and Duox1 in ASCs (Fig.…”
Section: Different Expression Of Nox Family Members Under Hypoxiamentioning
confidence: 99%
“…Of them, Nox4 is predominantly expressed in ASCs and functions as a switch between proliferation and differentiation of ASCs [34]. Nox4 modulates and generates ROS in insulin signaling and the expression of Nox4 is downregulated in the adipogenic differentiation of ASCs [35,36]. Although it has been known about the essential role of Nox4 in the adipogenic differentiation of ASCs, the Nox4-mediated stimulatory effect on ASCs has not been explored yet.…”
Section: Introductionmentioning
confidence: 99%